1996
DOI: 10.1143/ptp.95.203
|View full text |Cite
|
Sign up to set email alerts
|

Bosonization of Thirring Model in Arbitary Dimension

Abstract: We propose to use a novel master Lagrangian for performing the bosonization of the D-dimensional massive Thirring model in D = d + 1 ≥ 2 dimensions. It is shown that our master Lagrangian is able to relate the previous interpolating Lagrangians each other which have been recently used to show the equivalence of the massive Thirring model in (2+1) dimensions with the Maxwell-Chern-Simons theory. Starting from the phase-space path integral representation of the master Lagrangian, we give an alternative proof for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Actually, the 2+1 dimensional massive Thirring model can be bosonized into the Maxwell-Chern-Simons theory in which the gauge boson mass is generated through the Chern-Simons term without breaking the gauge invariance [44,26]. This scenario can be extended into the higher dimensional case [26,27]. In 3+1 dimensional case, it is shown [27] that the Thirring model can be mapped into the antisymmetric tensor gauge theory.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, the 2+1 dimensional massive Thirring model can be bosonized into the Maxwell-Chern-Simons theory in which the gauge boson mass is generated through the Chern-Simons term without breaking the gauge invariance [44,26]. This scenario can be extended into the higher dimensional case [26,27]. In 3+1 dimensional case, it is shown [27] that the Thirring model can be mapped into the antisymmetric tensor gauge theory.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Even in the case of β = 0, it has been shown that the kinetic term for the field A µ is generated due to radiative corrections [28], only when the fermion mass is dynamically generated in the chiral limit m 0 = 0. In the case of massive fermion, particularly very massive fermion, the generation of the kinetic term can be seen also through the procedure of bosonization [44,26,27]. To see the effect coming from the dynamical gauge field A µ , we have here introduced the kinetic term from the beginning.…”
Section: Limiting Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…But since this is a local symmetry, the mismatch should not worry us. In fact it is long known that even the Thirring model can be turned into a gauge theory by introducing auxiliary fields [12][13][14][15][16][17]. Of more relevance is the pairing of global symmetries, since these are connected with the existence of conserved charges.…”
mentioning
confidence: 99%
“…In an independent line of development this matter is clarified starting with a reformulation of the TM as a gauge theory [12][13][14][15]. Furthermore, the idea is generalized to arbitrary dimensions and the connection between several intermediate models is revealed using master Lagrangians [16,17]. In addition to the interest in the context of high-energy physics, the TM model appears frequently in condensed matter systems.…”
mentioning
confidence: 99%